A trifunctional linker suitable for conducting three orthogonal click chemistries in one pot. Issue 45 (27th October 2016) - Knall, Astrid-Caroline; Hollauf, Manuel; Saf, Robert; Slugovc, Christian
Abstract : A facile one-pot triple-click protocol involving mutually orthogonal azide–alkyne, tetrazine–alkene and Michael thiol–ene click reactions is presented. Abstract : The feasibility of a one pot approach for conducting mutually orthogonal thiol-Michael addition, copper catalyzed azide–alkyne and inverse electron demand Diels–Alder click chemistry on a tri-functional substrate was demonstrated.